Professional Education in Adolescent Period Psychological Characteristics (Zien Journal of Social Sciences and Humanities, 2022)
It consists in developing generalized conclusions, recommendations based on theoretical and practical analyzes of the problems of "psychological characteristics of professional knowledge in adolescence" and researching the scientific and practical aspects of the development of professional interests in accordance with the requirements of today's society and giving theoretical and practical psychological advice.